The Influence of Digital Transformation, Leadership Style, Organizational Culture, Work Environment, and Employee Attitudes on Employee Performance - Made Sekar Ayu Mia Arisandi; Rinto Rain Barry (Universitas Pelita Harapan, 2024)
Employee performance is a crucial aspect in achieving the goals of a company. The aim of this research is to identify the impact of various organizational factors on employee performance. Digital transformation, as a step for companies to adapt to technology, plays a significant role in improving work efficiency. Leadership style, organizational culture, and work environment also have a substantial influence in shaping employee attitudes and performance. This study employs a quantitative approach using a survey method, where data were collected from permanent employees at PT XYZ. The data were gathered from all permanent employees who had been working at XYZ Company in South Tangerang for at least one year, using a non-probability sampling technique. SPSS software was then used to analyze the research results. The findings indicate that all independent variables have a significant impact on employee performance. This study is expected to provide practical guidance for company management to enhance employee performance through the optimization of organizational factors. The research outcomes can offer managerial implications that will assist the company in improving employee performance. Several limitations are noted in this study, followed by recommendations for future research.